2019
DOI: 10.1021/acs.jmedchem.8b02008
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of a Novel Chemotype of Histone Lysine Methyltransferase EHMT1/2 (GLP/G9a) Inhibitors: Rational Design, Synthesis, Biological Evaluation, and Co-crystal Structure

Abstract: Since the discovery of compound BIX01294 over 10 years ago, only a very limited number of nonquinazoline inhibitors of H3K9-specific methyltransferases G9a and G9a-like protein (GLP) have been reported. Herein, we report the identification of a novel chemotype for G9a/GLP inhibitors, based on the underinvestigated 2-alkyl-5-aminoand 2-aryl-5-amino-substituted 3H-benzo[e][1,4]diazepine scaffold. Our research efforts resulted in the identification 12a (EML741), which not only maintained the high in vitro and cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 36 publications
(46 citation statements)
references
References 125 publications
0
38
0
Order By: Relevance
“…All compounds were dissolved in DMSO (100%) to obtain 50 mM solutions and diluted in HBS-P (10 mM HEPES pH 7.4, 0.15 M NaCl, 0.005% surfactant P20), always maintaining a final 0.2% DMSO concentration. Binding experiments were performed as previously described [62].…”
Section: Surface Plasmon Resonancementioning
confidence: 99%
“…All compounds were dissolved in DMSO (100%) to obtain 50 mM solutions and diluted in HBS-P (10 mM HEPES pH 7.4, 0.15 M NaCl, 0.005% surfactant P20), always maintaining a final 0.2% DMSO concentration. Binding experiments were performed as previously described [62].…”
Section: Surface Plasmon Resonancementioning
confidence: 99%
“…Given the evidence demonstrating the implication of the G9a/GLP complex in different human diseases, it has emerged as a promising pharmacological target, and several small-molecules have been designed to inhibit these enzymes [24]. Optimization of these molecules lead to UNC0642, a compound with IC 50 < 2.5 nM and optimized pharmacokinetics (PK) [24, 25]. This inhibitor of G9a/GLP was the first in vivo chemical probe with high potency in reducing H3K9me2 levels, and low cell toxicity (EC 50 > 3,000 nM).…”
Section: Introductionmentioning
confidence: 99%
“…Often G9a and GLP activities are described as inhibitory targets for cancer treatment (Casciello et al, 2015;Charles et al, 2019;Milite et al, 2019); for example, Huang and colleagues reported G9a and GLP to be overexpressed in a variety of cancers, denoting them as candidate oncogenes (Huang et al, 2010). Supporting this, a higher G9a expression has been correlated with poor prognosis in terms of clinicopathological features of gastric cancer and poor patient outcomes (Zhang et al, 2019).…”
Section: Hypoxic Methylation and Pathological Relevancementioning
confidence: 99%
“…The development of pharmacological inhibitors of G9a and/or GLP has resulted in a capability to selectively inhibit these KMTs ( Charles et al, 2019 ; Milite et al, 2019 ). However, caution in the use of G9a inhibition as a therapeutic strategy in cancer has recently been advocated ( Seton-Rogers, 2019 ).…”
Section: Hypoxic Methylation and Pathological Relevancementioning
confidence: 99%